2013
DOI: 10.1037/a0030389
|View full text |Cite
|
Sign up to set email alerts
|

How important are work–family support policies? A meta-analytic investigation of their effects on employee outcomes.

Abstract: This meta-analysis examines relationships between work-family support policies, which are policies that provide support for dependent care responsibilities, and employee outcomes by developing a conceptual model detailing the psychological mechanisms through which policy availability and use relate to work attitudes. Bivariate results indicated that availability and use of work-family support policies had modest positive relationships with job satisfaction, affective commitment, and intentions to stay. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
377
1
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(403 citation statements)
references
References 129 publications
18
377
1
7
Order By: Relevance
“…Especially because contemporary research has been limited to studying the effect of a special type of HRMP, such as those designed to alleviate the conflict between work and family. In this regard, the evidence published (Butts, Casper, & Yang, 2013) indicates that the availability and implementation of practices that promote positive articulation between work and family are associated with positive work attitudes, especially satisfaction. Odle-Dusseau, Britt and Greene-Shortridge (2012) have pointed out that when employees perceive that their supervisors facilitate an environment in which work and family can be handled harmoniously, they develop more positive work attitudes and improve performance significantly.…”
Section: Hrmp and Employees Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially because contemporary research has been limited to studying the effect of a special type of HRMP, such as those designed to alleviate the conflict between work and family. In this regard, the evidence published (Butts, Casper, & Yang, 2013) indicates that the availability and implementation of practices that promote positive articulation between work and family are associated with positive work attitudes, especially satisfaction. Odle-Dusseau, Britt and Greene-Shortridge (2012) have pointed out that when employees perceive that their supervisors facilitate an environment in which work and family can be handled harmoniously, they develop more positive work attitudes and improve performance significantly.…”
Section: Hrmp and Employees Job Satisfactionmentioning
confidence: 99%
“…Faced with such arguments, it was assumed that: H1: workers in companies whose HRMP are oriented to employees or to open systems will experience greater job satisfaction Results-oriented HRMP imply a state of permanent competition with a view to achieving predetermined objectives, which is why they favor a rigid division of tasks over the relaxation of processes and procedures. Alicia Omar, Solana Salessi, Florencia Urteaga Recent studies (Butts et al, 2013) have reported that work environments characterized by excessive labor demands and lack of collaboration and mutual help among those who perform different functions, generate high dissatisfaction. So, employees of organizations characterized by this type of HRMP, coupled with the enormous pressure for constant productivity, could experience lower levels of job satisfaction.…”
Section: Hrmp and Employees Job Satisfactionmentioning
confidence: 99%
“…Vários outros estudos identificaram a flexibilidade, no que diz respeito à gestão do tempo de trabalho, como promotora de sentimentos de autonomia e apoio vistos como benéficos, por parte dos colaboradores, para a boa gestão da vida familiar (Byron, 2005;Greenhaus, Parasuraman, Granrose, Rabinowitz, & Beutell, 1989;Lewis, & Cooper, 2005;Lewis, Rapoport, & Gambles, 2003). A este propósito vários estudos encontraram uma relação entre contextos profissionais com maior flexibilidade e possibilidade de controlo sobre os horários de trabalho como estando associados a menores percepções de tensão entre o trabalho e a vida familiar, por parte dos colaboradores, contribuindo, também, para um aumento da satisfação profissional dos mesmos (Butts, Casper, & Yang, 2013;Hill, Grzywacz, Allen, Blanchard, Matz-Costa, Shulkin, & PittCatsouphes, 2008;Kelly, Kossek, Hammer, Durham, Bray, Chermack, Murphy, &. Kaskubar, 2008;Kossek, Pichler, Bodner, & Hammer, 2011).…”
Section: Conciliação Trabalho-familia: Medidas E Práticas Organizaciounclassified
“…Multiple changes in the structure of families and the composition of the workforce, such as increasing numbers of dual-earner couples and new expectations of men as parents, have led many North American employees to experience difficulties reconciling the conflicting demands of their roles as workers and parents (Butts, Casper, & Yang, 2013;Janzen, Muhajarine, & Kelly, 2007). In addition, data from recent studies indicate that reconciling work and family is a major concern for working parents (Breaugh & Frye, 2008;St-Amour, Laverdure, Devault, & Manseau, 2005), particularly for managers and professionals, who are among the workers most at risk of experiencing high levels of interrole conflict (Duxbury & Higgins, 2003).…”
Section: Introductionmentioning
confidence: 99%